Burden of Staphylococcus aureus infections after orthopedic surgery in Germany - Fraence Hardtstock; Kirstin Heinrich; Thomas Wilke; Sabrina Mueller; Holly Yu (BMC Infectious Diseases, 2020)
Abstract Background This study assessed incidence, risk factors, and outcomes of Staphylococcus aureus infections (SAI) following endoprosthetic hip or knee, or spine surgeries. Methods Adult patients with at least one of the selected surgeries from 2012 to 2015 captured in a German sickness fund database were included. SAI were identified using S. aureus-specific ICD-10 codes. Patients with certain prior surgeries and infections were excluded. Cumulative incidence and incidence density of post-surgical SAI were assessed. Risk factors, mortality, healthcare resource utilization and direct costs were compared between SAI and non-SAI groups using multivariable analyses over the 1 year follow-up. Results Overall, 74,327 patients who underwent a knee (28.6%), hip (39.6%), or spine surgery (31.8%) were included. The majority were female (61.58%), with a mean age of 69.59 years and a mean Charlson Comorbidity Index (CCI) of 2.3. Overall, 1.92% of observed patients (20.20 SAI per 1000 person-years (PY)) experienced a SAI within 1 year of index hospitalization. Knee surgeries were associated with lower SAI risk compared with hip surgeries (Hazard Ratio (HR) = 0.8; p = 0.024), whereas spine surgeries did not differ significantly from hip surgeries. Compared with non-SAI group, the SAI group had on average 4.4 times the number of hospitalizations (3.1 vs. 0.7) and 7.7 times the number of hospital days (53.5 vs. 6.9) excluding the index hospitalization (p < 0.001). One year post-orthopedic mortality was 22.38% in the SAI and 5.31% in the non-SAI group (p < 0.001). The total medical costs were significantly higher in the SAI group compared to non-SAI group (42,834€ vs. 13,781€; p < 0.001). Adjusting for confounders, the SAI group had nearly 2 times the all-cause direct healthcare costs (exp(b) = 1.9; p < 0.001); and 1.72 times higher risk of death (HR = 1.72; p < 0.001). Conclusions SAI risk after orthopedic surgeries persists and is associated with significant economic burden and risk of mortality. Hence, risk reduction and prevention methods are of utmost importance.